 ## Recent Questions

110 views

### (cosec Theta - Sin Theta) (sec Theta - Cos Theta) = Sin Theta . Cos Theta

CBSE Discussions

Modified 1 Year Ago Stewart

123 views

### If M = Cos Theta - Sin Theta And N = Cos Theta + Sin Theta

CBSE Discussions

Modified 1 Year Ago Benjamin

108 views

### Show That 2 (sin (power 6) Theta + Cos (power 6) Theta) - 3 (sin (power 4) Theta + Cos (power 4) Theta) + 1 = 0

CBSE Discussions

Modified 1 Year Ago Benjamin

111 views

### If Cos Theta - Sin Theta = Underoot 2 Sin Theta, Prove That Cos Theta + Sin Theta

CBSE Discussions

Modified 1 Year Ago Robert

123 views

### If Sec Theta + Tan Theta = P, Show That Sec Theta - Tan Theta = 1/p

CBSE Discussions

Modified 1 Year Ago Ella

112 views

### Given That 2 Sin A Cos A + (cos A + Sin A) Square - (2 Cos A + Sin A) Square

CBSE Discussions

Modified 1 Year Ago Stephen

110 views

### (sin A /1 + Cos A + 1 + Cos A /sin A) (sin A / 1 - Cos A - 1 - Cos A /sin A)

CBSE Discussions

Modified 1 Year Ago Sean

108 views

### Sin A / 1 + Cos A + Sin A / 1- Cos A = Underoot 1 + Cos A / 1 - Cos A

CBSE Discussions

Modified 1 Year Ago Brian

110 views

### Q(p Square - 1) =2p, Where Sin Theta + Cos Theta = P And Sec Theta + Cosec Theta = Q

CBSE Discussions

Modified 1 Year Ago Julia

109 views

### Sin A + Sin B / Cos A + Cos B + Cos A - Cos B / Sin A - Sin B = 0

CBSE Discussions

Modified 1 Year Ago Ryan

117 views

### Cosec Theta + Cot Theta / Cosec Theta - Cot Theta = (cosec Theta + Cot Theta) Square

CBSE Discussions

Modified 1 Year Ago Victor

109 views

### Cos A / 1 - Tan A + Sin Square A / Sin A - Cos A = Sin A + Cos A

CBSE Discussions

Modified 1 Year Ago Amelia

109 views

### (tan Theta + Sec Theta - 1) (tan Theta + 1 + Sec Theta) = 2 Sin Theta / 1 - Sin Theta

CBSE Discussions

Modified 1 Year Ago Wendy

116 views

### 1 + Tan Cube Theta / 1 Tan Theta + Tan Theta - Sec Square Theta = 0

CBSE Discussions

Modified 1 Year Ago Indiresh

102 views

### Sec Square Theta - Sin Square Theta - 2 Sin (power 4) Theta / 2 Cos (power 4) Theta - Cos Square Theta = 1

CBSE Discussions

Modified 1 Year Ago Melanie

111 views

### Underoot Sec A - Tan A/sec A + Tan A Underoot Cosec A - Cot A / Cosec A + Cot A

CBSE Discussions

Modified 1 Year Ago Jake

95 views

### Underoot Sin A + 1/1 - Sin A + Underoot 1 - Sin A / Sin A + 1 = 2 Sec A

CBSE Discussions

Modified 1 Year Ago Karen

93 views

### 1 - Cos A + Sin A / Sin A + Cos A - 1 = 1 + Sin A / Cos A

CBSE Discussions

Modified 1 Year Ago Virginia

143 views

### Sec Square Theta - Sin Square Theta / Tan Square Theta = 1 + Cot Square Theta - Cos Square Theta

CBSE Discussions

Modified 1 Year Ago Stewart

124 views

### Tan Theta - Cot Theta = 2 Sin Square Theta - 1/sin Theta Cos Theta

CBSE Discussions

Modified 1 Year Ago Yvonne

120 views

### Tan Square Theta + Cot Square Theta + 2

CBSE Discussions

Modified 1 Year Ago Pippa

115 views

### (1 + Cot Theta - Cosec Theta) (1 + Tan Theta + Sec Theta) = 2

CBSE Discussions

Modified 1 Year Ago Una

106 views

### (1 + Tan Square Theta) + (1+ 1/tan Square Theta) = 1/sin Square Theta - Sin (power 4) Theta

CBSE Discussions

Modified 1 Year Ago Vanessa

103 views

### Find The Values Of The Constant A And B For Which Sin X Into Cos X (5 Tan X + 2 Cot X)

CBSE Discussions

Modified 1 Year Ago Frank

97 views

### If Cot A / 1 + Cosec A - Cot A /1 - Cosec A = K/cos A, Then Find The Value Of K

CBSE Discussions

Modified 1 Year Ago Carolyn

120 views

### 1 - Cos Theta /1 + Cos Theta = ( Cosec Theta - Cot Theta) Square

CBSE Discussions

Modified 1 Year Ago Austin

97 views

### Underoot (1- Cos Square Theta) Sec Square Theta = Tan Theta

CBSE Discussions

Modified 1 Year Ago Ava

98 views

### Cos Theta / 1 + Sin Theta = 1 - Sin Theta / Cos Theta

CBSE Discussions

Modified 1 Year Ago Pippa

104 views

### Sin Theta / 1 + Cos Theta + 1 + Cos Theta / Sin Theta = 2 Cosec Theta

CBSE Discussions

Modified 1 Year Ago Benjamin

108 views

### (1- Sin A + Cos A) Square = 2 (1- Sin A)

CBSE Discussions

Modified 1 Year Ago Oliver 